All Days 2015
DOI: 10.4043/26047-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Paraffin Deposition under Two-Phase Gas-Oil Slug Flow in Horizontal Pipes

Abstract: Paraffin or wax deposition under two-phase gas-oil slug flow in horizontal pipes was studied experimentally. The experiments were conducted using a 2.067-in large-scale multiphase flow loop under an operating pressure of 350 psig. Testing fluids were Garden Banks condensate and natural gas. Hydrodynamic experiments were performed prior to the wax deposition experiments to verify the flow patterns and examine the flow behavior. The hydrodynamic and heat-transfer variables were estimated using the unified mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…In contrast, the deposition-hindering factor is attributed to the surface area of the crude oil pipeline which is in-contact with the oil when the liquid holdup decreases as the gas velocity increases. Few studies have found that the deposition-hindering factor is amplified for bubbly, wavy, and intermittent flow patterns [49,54].…”
Section: Wax Deposition In Multiphase Flowmentioning
confidence: 99%
“…In contrast, the deposition-hindering factor is attributed to the surface area of the crude oil pipeline which is in-contact with the oil when the liquid holdup decreases as the gas velocity increases. Few studies have found that the deposition-hindering factor is amplified for bubbly, wavy, and intermittent flow patterns [49,54].…”
Section: Wax Deposition In Multiphase Flowmentioning
confidence: 99%
“…Wax deposition models are developed based on consideration of assumptions and selection of parameters. Four main models are discussed in this book chapter: film mass transfer model (FMTM), equilibrium model (EM), Matzain's model (MM), and Venkatesan's model (VM) [24][25][26][27][28].…”
Section: Wax Deposition Modelsmentioning
confidence: 99%
“…Matzain et al [8], Apte et al [9] and Rittirong [10] observed that the wax deposit only buildup on the wall wetted by the oil, and there was no deposit on the wall wetted by gas, and the deposit emerged a crescent shape at the pipe cross section, through the wax deposition in oil-gas stratified flow experiment. A semi-empirical model for wax deposit in oil-gas stratified flow was developed, based on the molecule diffusion mechanism and the assumption that all precipitated wax crystals on pipeline wall can deposit.…”
Section: Introductionmentioning
confidence: 98%
“…A semi-empirical model for wax deposit in oil-gas stratified flow was developed, based on the molecule diffusion mechanism and the assumption that all precipitated wax crystals on pipeline wall can deposit. The model takes the mutual effect of molecule diffusion and shear dispersion into consideration [9][10][11]. The wax deposit experiment for oil-gas stratified flow was also carried out by Gong et al [12] with Daqing crude oil and air.…”
Section: Introductionmentioning
confidence: 99%